Acute superior mesenteric vein thrombosis associated with abdominal trauma: A rare case report and literature review. Issue 47 (November 2017) - Lim, Kyoung Hoon; Jang, Jihoon; Yoon, Hye Young; Park, Jinyoung
Abstract: Rationale: Acute mesenteric vein thrombosis (MVT) is defined as new-onset thrombosis of the mesenteric vein without evidence of collateralization, finally resulting in extensive intestinal infarction. MVT may be idiopathic or be caused by conditions responsible for thrombophilia and acquired risk factors. To date, there have been few reports of MVT after trauma. Herein we describe our experiences treating three patients with MVT. Patient concerns: Case 1 was a 44-year-old man with transverse colon mesenteric hematoma after blunt abdominal trauma. Case 2 was a 55-year-old man with jejunal transection after a traffic accident. Case 3 was a 26-year-old man presented with multiple abdominal stab bowel injury. Diagnoses: A 1-week follow-up abdominal computed tomography scan showed superior mesenteric vein thrombosis in all of three patients. Interventions: All patients were treated with anticoagulant for 3 or 6 months. Outcomes: MVTs were completely resolved without any complications. Lessons: If early diagnosis and treatment could be available, anticoagulation alone might be adequate for the treatment of SMVT associated with trauma. Early anticoagulation in patients with acute SMVT may avoid the grave prognosis observed in patients with arterial thrombosis.